Selective and stable bimetallic PtSn/theta-Al2O3 catalyst for dehydrogenation of n-butane to n-butenes - Nagaraja, Bhari Mallanna; Shin, Chae-Ho; Jung, Kwang-Deog (ELSEVIER, 2013)
PtSn/theta-Al2O3 with various Pt and Sn compositions was prepared by a co-impregnation method using theta-Al2O3 support for n-butane dehydrogenation reaction. The monometallic Pt-1.5/theta-Al2O3 catalyst showed severe deactivation in n-butane dehydrogenation. The bimetallic PtSn/theta-Al2O3 catalyst improved the n-C-4(2-) yield and the stability. The compositions listed in order of n-C-4(2-) yield at 823 K are as follows: (PtSn)(1.5) > (PtSn)(1.0) > (PtSn)(2.0) > (PtSn)(0.5) > Pt-1.5 > Snis. The n-C-4(2-) yields increased with the specific metal surface area. The Sn loading was varied on the Pt-1.5 loaded catalyst. Then, the compositions listed in order of n-C-4(2-) yield at 823 K were as follows: (PtSn)(1.5) > Pt1.5Sn1.0 > Pt1.5Sn2.0 > Pt1.5Sn0.5 > Pt-1.5. The n-C-4(2-) yield was maximized at a Pt/Sn weight ratio of 1.0. The n-C-4(2-) selectivity of the Pt-1.5 catalyst was substantially improved by the Sn addition. TEM and XRD studies indicated PtSn alloy formation on the bimetallic PtSn catalysts during the reduction. The PtSn alloy can increase the n-C-4(2-) selectivity by blocking the cracking and hydrogenolysis sites of the Pt catalyst. TPR and HAADF STEM-EDS studies suggest the reduction procedure of the Pt and Sn species. The scattered Pt oxides in the vicinity of the well-dispersed Sn oxides were co-reduced, and then the reduced Sn metals migrated to the PtSn particles, resulting in a PtSn alloy. The specific metal surface area of the Pt-1.5 sample was much lower than that of the (PtSn)(1.5) sample. Therefore, it can be suggested that Pt metal sintering can be retarded by PtSn alloy formation during the reduction, resulting in high specific metal surface area. These observations demonstrate that the addition of Sn can enhance the activity and n-C-4(2-) selectivity. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: ISOBUTANE DEHYDROGENATION; PT-SN/AL2O3 CATALYSTS; PTSNK/GAMMA-AL2O3 CATALYST; PT/SN CATALYSTS; ALUMINA; PLATINUM; SN; PERFORMANCE; ZIRCONIA; HYDROGEN